HUBUNGAN LINGKUNGAN RUMAH DENGAN KEJADIAN DIARE PADA BALITA - Syafriani Syafriani; Afiah Afiah; Nia Aprilla (Universitas Pahlawan Tuanku Tambusai, 2021)
Diarrhea is one of the main public health problems in Indonesia which is one of the second largest causes of death in infants and children. In Indonesia, around 162 thousand toddlers and children die every year or about 460 toddlers and children per day. Outbreaks of diarrhea often hit the people of Indonesia, because Indonesia is an endemic area of diarrhea caused by climate change and poor environmental health. The purpose of this study was to determine the relationship between the home environment and the incidence of diarrhea in children under five. The research design used a cross-sectional research design with a sample of 60 houses whose mothers could be used as respondents. The results of the study on 60 mothers concluded that there were 32 houses in an unhealthy environment (53.3%), a healthy environment in 28 houses (46.7%). For the incidence of diarrhea as many as 20 people (33.3%) and who did not experience diarrhea as many as 40 people (66.7%). Chi Square statistical test to see the relationship between the environment and the incidence of diarrhea proved statistically significant with p value = 0.001. Families are expected to actively seek information from the nearest health service and various media as well as the need for high awareness in preventing diarrheal disease.